2018
DOI: 10.1080/17470218.2016.1255236
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual-cognitive skill and the in situ performance of soccer players

Abstract: Many studies have shown that experts possess better perceptual-cognitive skills than novices (e.g., in anticipation, decision making, pattern recall), but it remains unclear whether a relationship exists between performance on those tests of perceptual-cognitive skill and actual on-field performance. In this study, we assessed the in situ performance of skilled soccer players and related the outcomes to measures of anticipation, decision making, and pattern recall. In addition, we examined gaze behaviour when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 52 publications
4
49
0
Order By: Relevance
“…Gaze measures suggested that peripheral vision may serve a significant role in decision making in situ, whereas players mainly relied on central vision to execute an action. Collectively, these results confirm the earlier suggestions that in situ research designs should be used to accurately capture perceptual-motor performance of athletes (Dicks et al, 2010;Mann & Savelsbergh, 2015;Mann et al, 2007Mann et al, , 2010Pinder et al, 2015;Travassos et al, 2013;Van Maarseveen et al, 2016;Williams & Ericsson, 2005), and more advanced gaze analysis methods should be used to enhance our understanding of visual search (Mann et al, 2009). This study showed that decision-making skill and gaze behaviour can be measured successfully in situ, since the results revealed that wearing the eye tracking glasses did not influence the decisions of the players nor the quality of their decisions.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Gaze measures suggested that peripheral vision may serve a significant role in decision making in situ, whereas players mainly relied on central vision to execute an action. Collectively, these results confirm the earlier suggestions that in situ research designs should be used to accurately capture perceptual-motor performance of athletes (Dicks et al, 2010;Mann & Savelsbergh, 2015;Mann et al, 2007Mann et al, , 2010Pinder et al, 2015;Travassos et al, 2013;Van Maarseveen et al, 2016;Williams & Ericsson, 2005), and more advanced gaze analysis methods should be used to enhance our understanding of visual search (Mann et al, 2009). This study showed that decision-making skill and gaze behaviour can be measured successfully in situ, since the results revealed that wearing the eye tracking glasses did not influence the decisions of the players nor the quality of their decisions.…”
Section: Discussionsupporting
confidence: 84%
“…As such, this study shows that using eye tracking in situ does not (necessarily) interfere with task execution and performance, implying that eye tracking provides a powerful tool to investigate the relationship between perception, decision-making and action in situ, also in complex sports contexts. The availability of such a tool is in line with earlier suggestions that in situ research designs should be used to accurately capture perceptual-motor performance of athletes (Dicks et al, 2010;Mann & Savelsbergh, 2015;Mann et al, 2007Mann et al, , 2010Pinder et al, 2015;Travassos et al, 2013;Van Maarseveen et al, 2016;Williams & Ericsson, 2005), and opens up many opportunities for future research.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Despite the consistency of these findings, we know very little about how these skills are trained ( Williams and Grant, 1999 ; Schorer et al, 2015 ). Previous studies of perceptual training in sport have focused on the influence of different forms of instruction ( Smeeton et al, 2005 ; Abernethy et al, 2012 ) or feedback ( Memmert et al, 2009 ; Schorer et al, 2010 ), as well as transfer from the laboratory to field settings ( Scott et al, 1998 ; Williams et al, 2003 ; van Maarseveen et al, 2016 ) or from virtual realities to reality ( Tirp et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%